STRATEGI PENGEMBANGAN KARAKTER SISWA MELALUI EKSTRAKURIKULER KARAWITAN DI SEKOLAH DASAR NEGERI 3 KERAMBITAN - Anak Agung Adi Risanta Darma; I Ketut Sudarsana (Widyacarya: Jurnal Pendidikan, Agama dan Budaya, 2022)
The purpose of this study was to determine the strategy of character development of students through extracurricular karawitan at the State Elementary School 3 Kerambitan. Motivation to learn greatly determines the teaching and learning process in the classroom. Student teaching strategies are very influential in motivating student learning. The learning process that is too monotonous causes a lack of interest in student learning. Therefore we need a learning media that can generate student learning motivation. This type of research is a qualitative research with data collection methods using the methods of 1) interviews, 2) observation, 3) documentation. The results of the study indicate that the strategy of developing student character through extracurricular karawitan at the State Elementary School 3 Kerambitan, namely: exemplary, empowerment and civilizing, strengthening. Characters developed in students through musical extracurricular activities include: religiosity, justice, honesty, fighting power, responsibility. Supporting factors in developing student character through extracurricular karawitan at the State Elementary School 3 Kerambitan are: school support, government support, parental and community support.